Enamel ultrastructure of lower molars of the red squirrel Sciurus vulgaris (Mammalia, Rodentia) from different populations in Ukraine - Rekovets, L.; Kovalchuk, O.; Demeshkant, V.; Shevchenko, L. (Theriologia Ukrainica, 2019)
The second lower molars of the red squirrel Sciurus vulgaris from different regions of Ukraine were examined in order to search for additional features to study the variability and clarify the subspecies status of its individual populations. Generally accepted methods were used to study the enamel ultrastructure. It is established that the tooth enamel of the red squirrel has a layered structure and is represented by different types (radial, HSB and PLEX), which are also characteristic for other rodent species. The arrangement of crystalline prisms of the radial layer in the IPM matrix is the main distinguishing feature of the morphological variability of enamel on main tooth conids. In various regional populations of the species, they act as an indicator of the adaptability of the teeth and their functionality as a single structure. This was reflected in differences in the thickness ratio of the radial layer and HSB, especially between the metaconid and the entoconid. The development of HSB is usually associated with greater functional load. Squirrel populations in the northern part of Ukraine have a relatively thick HSB layer, while those from central and southern parts of the country have a more strongly developed radial layer. According to these features, the Crimean populations are close to those from southern Ukraine and slightly differ from the Altai subspecies Sciurus vulgaris exalbidus, which was introduced into the Crimea in the first half of XX century. It is assumed that the enamel ultrastructure as a morphological character has changed in the process of adaptation of squirrels to a new environment. The distinguishing character of the enamel structure of Altai populations of the Teleut squirrel is that prisms do not fill cells of the radial layer on the hypoconid and protoconid. The tooth enamel ultrastructure of the Eurasian red squirrel cannot be an independent morphological character for their intraspecific differentiation. However, it can be successfully used in combination with other characters (e.g., fur coloration, craniometrical data), as well as the results of special molecular studies.. Досліджували корінні зуби (нижні м2) вивірки звичайної Sciurus vulgaris різних регіонів України з метою пошуку додаткових ознак для вивчення мінливості і уточнення підвидового статусу окремих популяцій. Використано загальноприйняті методики вивчення ультраструктури емалі зубів. Встановлено, що емаль зубів цього виду має шарувату структуру і представлена різними типами (радіальна, HSB i PLEX), які властиві також іншим видам гризунів. Особливості розміщення кристалічних призм радіального шару в матриці IPМ є основними ознаками мінливості морфології емалі, особливо на основних конідах зубів. У локальних популяціях виду з різних регіонів структура емалі є подібною і виступає показником адаптивності зубів як єдиної функціональної структури. Певною мірою така мінливість відбилася на відмінностях у співвідношенні товщини радіального шару і HSB, особливо між метаконідом та ентоконідом. Розвиток HSB, як правило, пов’язаний із виконанням більшого функціонального навантаження. Популяції північної частини України мають порівняно товстий шар HSB, а центральної та південної частини – більш розвинений радіальний шар. Кримські популяції за цими показниками близькі до південноукраїнських і відрізняються від алтайського підвиду S. vulgaris exalbidus, який був інтродукований до Криму в першій половині ХХ століття. Висловлено припущення, що ультраструктура емалі як морфологічна ознака зазнала змін у процесі адаптації вивірок до нових умов. Відмінною рисою структури емалі вивірки з алтайської популяції є те, що чарунки радіального шару на гіпо- та протоконіді не заповнені призмами. Ультраструктура емалі зубів вивірки не може розглядатися у якості незалежної морфологічної ознаки для внутрішньовидової диференціації. Водночас, вона може бути застосована у поєднанні з забарвленням хутра, краніометричними даними, а також результатами молекулярних досліджень.